Agrogetaway Web Application - Ddumba, Timothy; Gortland, Jim James; Tryphine, Nalule; Josephine, Namuwonge; Joan, Nabirye; Adam, Murungi (Uganda Christian University, 2024)
The Agrogetaway project is an innovative initiative aimed at transforming the agricultural landscape by leveraging technology to facilitate knowledge exchange between farmers and agricultural enthusiasts. This web-based platform serves as a conduit for sharing best practices, advanced farming techniques, and practical knowledge through an interactive and user-friendly interface. The project's cornerstone is the creation of a digital community where users can book farm tours, access a wealth of educational resources, and engage in real-time discussions with experienced model farm managers. Agrogetaway addresses the critical challenge of improving agricultural produce quality in Uganda, which directly impacts the nation's competitiveness in the global market and its food security. By connecting users with model farmers and providing a repository of multimedia educational content, the platform fosters a collaborative environment for learning and growth. The project also introduces a novel feature, 'Communities,' structured around model farmers, where users can subscribe for exclusive insights and direct mentorship. The platform's development followed a mixed-methods approach, incorporating both qualitative and quantitative research to ensure comprehensive user-centric design and functionality. Evaluations indicate user satisfaction and a gradual increase in engagement, although challenges such as a lack of scientific depth and device compatibility were identified. Recommendations for future enhancements include infrastructure improvements, user education programs, and advanced security measures. Agrogetaway's vision is to empower farmers with the knowledge and tools necessary to enhance productivity and sustainability, ultimately contributing to the advancement of the agricultural sector. The project's ongoing development and research aim to expand its reach, improve user experience, and solidify its position as an indispensable resource for modern agriculture.